Effects of the material properties and thickness on the minimum formable radius in the subtle feature forming process. Issue 4 (April 2023) - Chung, Yun-Chan; Yu, Jae-Hyeong; Jung, Kyu-Seok; Song, Yong-Ho; Jun, Young-Bae; Kim, Young-Jae; Jun, Sung-Min; Kwon, Sung-Oh; Lee, Chang-Whan
Abstract: The subtle feature geometry also called a feature line, is considered an important geometric characteristic of automotive outer panels. The influences of material properties and thickness on the radius of curvature of subtle features were investigated in this study. First, the stamping process was simplified to a combined forming process between tensile and bending deformation. Subsequently, test materials, namely, 180B2, 210B2, CR2, CR3, and CR4, with various thickness values were adopted in the finite element analysis and experiments. In addition, the radius of curvature with respect to the material, thickness, punch radius, and punch angle was studied. The simulation results were compared with the experimental results for verification. From this comparison, it was found that the simulation results were in good agreement with the experimental data. Finally, the forming characteristics of the subtle feature-forming process were investigated to determine the effects of the material properties and thickness on the radius of curvature. The reason for the minimum formable radius when the radius of the punch was zero was studied. The results showed that, as the material thickness increased, more concentrated deformation occurred in the central region. In contrast, the radius of curvature of the subtle features increased as the thickness of the central region decreased. Similarly, decreased n-value results were identified for the same reason as the increased radius of curvature.